Thermal‐Stable Separators: Design Principles and Strategies Towards Safe Lithium‐Ion Battery Operations. Issue 24 (15th November 2022) - Lin, Wanxin; Wang, Feng; Wang, Huibo; Li, Heng; Fan, You; Chan, Dan; Chen, Shuwei; Tang, Yuxin; Zhang, Yanyan
Abstract: Lithium‐ion batteries (LIBs) are momentous energy storage devices, which have been rapidly developed due to their high energy density, long lifetime, and low self‐discharge rate. However, the frequent occurrence of fire accidents in laptops, electric vehicles, and mobile phones caused by thermal runaway of the inside batteries constantly reminds us of the urgency in pursuing high‐safety LIBs with high performance. To this end, this Review surveyed the state‐of‐the‐art developments of high‐temperature‐resistant separators for highly safe LIBs with excellent electrochemical performance. Firstly, the basic properties of separators (e. g., thickness, porosity, pore size, wettability, mechanical strength, and thermal stability) in constructing commercialized LIBs were introduced. Secondly, the working mechanisms of advanced separators with different melting points acting in the thermal runaway stage were discussed in terms of improving battery safety. Thirdly, rational design strategies for constructing high‐temperature‐resistant separators for LIBs with high safety were summarized and discussed, including graft modification, blend modification, and multilayer composite modification strategies. Finally, the current obstacles and future research directions in the field of high‐temperature‐resistant separators were highlighted. These design ideas are expected to be applied to other types of high‐temperature‐resistant energy storage systems working under extreme conditions. Abstract : Beat the heat : This Review presents the state‐of‐the‐art developments of high‐temperature‐resistant separators for highly safe lithium‐ion batteries with excellent electrochemical performance. These design concepts are envisioned to be applied to other energy storage systems in pursuit of better heat resistance and electrochemical performance.